Onset of fluidization in vertically shaken granular material - Pöschel, Thorsten; Schwager, Thomas; Salueña, Clara (Physical Review E, 2000)
Convection, surface fluidization, spontaneous heap formation, and other effects are analyzed when a granular material is shaken vertically. The existence of a threshold for the Froude number Γ = Aω-0//g is investigated, below which these effects cannot be observed. It is proved that there is no such threshold using computer simulation.